2011
DOI: 10.1007/978-1-61779-188-8_21
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Human Papillomavirus Expression Using DNAzymes

Abstract: Deoxyribozymes (DXZs) are catalytic oligodeoxynucleotides capable of performing diverse functions including the specific cleavage of a target RNA. These molecules represent a new type of therapeutic oligonucleotides combining the efficiency of ribozymes and the intracellular endurance and simplicity of modified antisense oligonucleotides. Commonly used DXZs include the 8-17 and 10-23 motifs, which have been engineered to destroy disease-associated genes with remarkable efficiency. Targeting DXZs to disease-ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Because of deleterious off-target effects in intracellular milieu of an otherwise specific and proven catalytic molecule against HPV in biochemical assays, the pursuit to make this class of molecules as potential therapeutics faded considerably. To overcome problems encountered with ribozymes, alternative molecules particularly the DNAzymes were explored (123,124). DNAzymes combined the efficiency of ribozymes and intracellular stability and simplicity of AS-ODNs (125).…”
Section: Silencing Hpv Rna By Catalytic Oligonucleotidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of deleterious off-target effects in intracellular milieu of an otherwise specific and proven catalytic molecule against HPV in biochemical assays, the pursuit to make this class of molecules as potential therapeutics faded considerably. To overcome problems encountered with ribozymes, alternative molecules particularly the DNAzymes were explored (123,124). DNAzymes combined the efficiency of ribozymes and intracellular stability and simplicity of AS-ODNs (125).…”
Section: Silencing Hpv Rna By Catalytic Oligonucleotidesmentioning
confidence: 99%
“…DNAzymes combined the efficiency of ribozymes and intracellular stability and simplicity of AS-ODNs (125). Out of the two commonly used DNAzymes, a widely used and well-characterized 10-23 motif has been engineered to destroy HPV oncogenes (123,124). DNAzyme Dz1023-434 showed efficient cleavage against HPV-16 E6/E7 mRNA within bona fide antisense window at nt 410-445 even in low (Mg ++ ) condition cell free systems.…”
Section: Silencing Hpv Rna By Catalytic Oligonucleotidesmentioning
confidence: 99%
“…8 Nowadays, the 10-23 DNAzymes have been widely employed to inhibit protein expression in experiments. 9,10 Recent studies have demonstrated that LMP1 expression can be suppressed by LMP1-targeted DNAzymes, which stimulate cell apoptosis, 11,12 inhibit cell proliferation and xenograft growth in nude mice, 13 and enhance radiosensitivity in NPC. 14 DNAzymes feature design simplicity, target-specific cleavage, serum stability, and catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Deoxyribozymes (DNAzymes, DZs) are synthetic single‐stranded DNA catalysts that can be bound to their complementary sequences in a target messenger RNA (mRNA) by Watson‐Crick base pairing and cleave the mRNA with predetermined phosphodiester linkages 8 . Nowadays, the 10‐23 DNAzymes have been widely employed to inhibit protein expression in experiments 9,10 . Recent studies have demonstrated that LMP1 expression can be suppressed by LMP1‐targeted DNAzymes, which stimulate cell apoptosis, 11,12 inhibit cell proliferation and xenograft growth in nude mice, 13 and enhance radiosensitivity in NPC 14 .…”
Section: Introductionmentioning
confidence: 99%